Severe Respiratory Distress in a Child with Pulmonary Idiopathic Hemosiderosis Initially Presenting with Iron-Deficiency Anemia - A. Potalivo; L. Finessi; F. Facondini; A. Lupo; C. Andreoni; G. Giuliani; C. Cavicchi (Case Reports in Pulmonology)
Idiopathic pulmonary hemosiderosis (IPH) is a rare cause of alveolar hemorrhage in children but should be considered in children with anemia of unknown origin who develop respiratory complications. It is commonly characterized by the triad of recurrent hemoptysis, diffuse parenchymal infiltrates, and iron-deficiency anemia. Pathogenesis is unclear and diagnosis may be difficult along with a variable clinical course. A 6-year-old boy was admitted to the hospital with a severe iron-deficiency anemia, but he later developed severe acute respiratory failure and hemoptysis requiring intubation and mechanical ventilation. The suspicion of IPH led to the use of immunosuppressive therapy with high dose of corticosteroids with rapid improvement in clinical condition and discharge from hospital.